Implementasi Pengenalan Pergerakan Bola Mata Menggunakan Elektroda Dengan Exponential Filter - Ichwanul Muchlis; Rizal Maulana; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Basically a human being is a social creature that needs each other. Surely every human must expect a normal life with a healthy body. A person who loses a physical or a physical disability will definitely be a challenge for them to be able to live social life with other people. Some patients with disabilities, especially those with disabilities, need a tool to enable them to interact normally with the help of rehabilitation tools. The design of rehabilitation tools utilizes from one of the intelligent bio-signal systems ie electrooculographic signal measurement techniques to record the electrical activity of eye movements. The hardware implementation uses five electrode sensors affixed around the eyes, an instrumentation amplifier OP07 with 416 amplification accompanied by high pass filter order 2 cutoff frequency 0.1Hz and low pass filter 2nd order 16Hz cutoff frequency and voltage source of the 9V circuit. Using the baseline method with a combination of calculating the exponential filter and threshold weight values. There is a process of designing and implementing hardware in a printed circuit board. The first software with the search for baseline values ​​of both channels, the process of calculating the weight value of 0.3 exponential filter for the noise can be resolved correctly and issued more accurate results, the determination of the five categories of eye movement ie front, right, left, top, and bottom with threshold value. The results of the test indicate that the first test of each eye movement is performed on 3 subjects reaching an average accuracy rate of 98.66%, the second of 5 consecutive eye movements performed on 3 subjects reaching an average accuracy rate of 96% and the third delay testing reaching flat the accuracy rate of 93.33%.